2024
DOI: 10.1007/s00018-024-05121-6
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine’s rapid and sustained antidepressant effects are driven by distinct mechanisms

Radhika Rawat,
Elif Tunc-Ozcan,
Sara Dunlop
et al.

Abstract: Administration of multiple subanesthetic doses of ketamine increases the duration of antidepressant effects relative to a single ketamine dose, but the mechanisms mediating this sustained effect are unclear. Here, we demonstrate that ketamine’s rapid and sustained effects on affective behavior are mediated by separate and temporally distinct mechanisms. The rapid effects of a single dose of ketamine result from increased activity of immature neurons in the hippocampal dentate gyrus without an increase in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…A study by Reed et al [ 23 ] used functional magnetic resonance imaging (fMRI) to demonstrate that ketamine administration led to increased activation in the prefrontal cortex, a region associated with emotional regulation and cognitive control [ 23 ]. Another study by Rawat et al [ 24 ] utilized structural MRI to show that ketamine induced rapid and transient increases in hippocampal volume, suggesting a potential role in promoting neurogenesis and synaptic plasticity [ 24 ]. Scheidegger et al [ 25 ] found that ketamine administration reduced amygdala hyperactivity, a common feature of mood disorders, and restored normal fear responses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Reed et al [ 23 ] used functional magnetic resonance imaging (fMRI) to demonstrate that ketamine administration led to increased activation in the prefrontal cortex, a region associated with emotional regulation and cognitive control [ 23 ]. Another study by Rawat et al [ 24 ] utilized structural MRI to show that ketamine induced rapid and transient increases in hippocampal volume, suggesting a potential role in promoting neurogenesis and synaptic plasticity [ 24 ]. Scheidegger et al [ 25 ] found that ketamine administration reduced amygdala hyperactivity, a common feature of mood disorders, and restored normal fear responses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous ketamine and intranasal esketamine did not differ in this aspect. Rawat et al discussed the accumulation of the antidepressant effect, suggesting that it was associated with changes in bone morphogenetic protein signaling (Rawat et al, 2024).…”
Section: Introductionmentioning
confidence: 99%